solve it ahead please I will mark e us brainliest
Attachments:
![](https://hi-static.z-dn.net/files/dd3/e50dfbc24bb8436f3163e485a0c60b3a.jpg)
aarchi82:
where is khushis answer
Answers
Answered by
0
go through it,i tried my best
Attachments:
![](https://hi-static.z-dn.net/files/da1/db0abf5b4cfa6192a63674689da77c15.jpg)
Answered by
1
Answer:
x = -4/3, 1/8
Step-by-step explanation:
Given: [4x - 3/2x + 1] - 10[2x + 1/4x - 3] = 3
⇒ (4x - 3)² - 10(2x + 1)² = 3(2x + 1)(4x - 3)
⇒ 16x² + 9 - 24x - 10[4x² + 1 + 4x] = 3[8x² - 6x + 4x - 3]
⇒ 16x² + 9 - 24x - 40x² - 10 - 40x = 24x² - 6x - 9
⇒ -24x² - 64x - 1 = 24x² - 6x - 9
⇒ -48x² - 58x + 8 = 0
⇒ 48x² + 58x - 8 = 0
⇒ 2(24x² + 29x - 8) = 0
⇒ 24x² + 29x - 8 = 0
⇒ 24x² - 3x + 32x - 8 = 0
⇒ 3x(8x - 1) + 4(8x - 1) = 0
⇒ (3x + 4)(8x - 1) = 0
⇒ x = -4/3, 1/8.
Hope it helps!
Similar questions